Evaluating The Rights Of Taxpayers Under The Income Tax Law No. 24 Of 2003 And Its Amendments - الضابط, مدين (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of this research is to evaluate the rights of taxpayers in the Syrian tax legislation, especially the Income Tax Law No. (24) for the year 2003 and its amendments, and related laws. The evaluation process includes the availability of these rights from a legislative point of view, on the other hand, to ensure the extent of their application in practice by the tax administration. A set of fundamental rights have been identified and agreed to by most tax systems, in addition to the statement of the Organization for Economic Cooperation and Development that has been adopted as a reference document in this field. These rights are the right to information, assistance, and listening, the right to appeal, the right to pay no more than the correct amount of tax, the right to certainty, the right to privacy, the right to confidentiality and confidentiality. The descriptive approach was mainly used in constructing the problem of this research and developing its hypotheses. In addition to using research tools such as personal interviews that included many employees in the tax administration, and access to some practical cases in that administration, in addition to the questionnaire that included a sample of taxpayer income. The data collected was analyzed using the SPSS statistical program and the Likert binary scale. The results of this research have shown that the Income Tax Law No. 24 of 2003 and other related laws have not explicitly, clearly and completely stipulated most of these rights, and their non-application by the tax administration. These rights are the right of the taxpayer to obtain information, assistance and listening, the right to certainty, the right of the taxpayer to pay no more than the correct amount of taxes, and the right to privacy. It also showed the important imbalance in the right to object, and stipulated the right to confidentiality only.